Adaptive fuzzy environmental control system for smart home - Ahmad Nasir, Che Rosli; Mohd Shaiful Aziz, Rashid Ali; Mohamad Faiz, Mohamad Lazi; Nor Amin, Mohd; Hobibi Husain, Arifin (Universiti Teknologi MARA, Kedah, 2010)
Invention, Innovation & Design (IID Kedah 2010), 28th - 29th July 2010 organized by Universiti Teknologi MARA (UiTM), Kedah at SP Inn, Kedah.